Clinical outcomes following surgical fixation of acromion fractures - Tram L. Tran, MD, MPH; Molly G. Sekar, MD; Nik Bhardwaja, BS; Jessica McGraw-Heinrich, MD; Michael D. McKee, MD; Niloofar Dehghan, MD (JSES International)
Background: Acromial fractures are rare in the traumatic setting; however, they have recently gained attention due to the increase in incidence as a result of a postoperative complication of reverse total shoulder arthroplasty. While historically these fractures were routinely treated nonoperatively, there is evidence that surgery can improve outcomes. The study aims to evaluate clinical outcomes following surgical treatment of acromion fractures and compare outcomes among patients with an intact rotator cuff against those with a deficient rotator cuff or reverse shoulder arthroplasty. Methods: This is a retrospective review of patients with acromion fractures that were treated with open reduction internal fixation between January 2014 and March 2023. Patients were stratified into three cohorts as follows: 1) rotator cuff intact; 2) rotator cuff impaired; and 3) presence of reverse total shoulder arthroplasty. Results: Thirty-seven patients were included in the study with a mean follow-up of 9 months (range 0.5-77). The mechanism of injury was stress fracture (46%), high-energy trauma (32%), or low-energy falls (22%). The mean time to surgery was 6 months (0-24). Older age and female sex were associated with stress fractures (P < .05). The odds of having a stress fracture were higher in patients with an impaired rotator cuff (OR 6.5, P = .04) or reverse total shoulder arthroplasty (OR 2.8, P = .02) compared to those with an intact rotator cuff. The mean shoulder flexion improved from 81 degrees preoperatively to 113 degrees at the time of the last visit (P = .02). The mean shoulder external rotation improved from 24 degrees preoperatively to 48 degrees at the time of the last visit (P = .04). The nonunion rate was 19% (7 of 37) and the reoperation rate was 11% (4 of 37) for removal of broken hardware or nonunion revision. Two patients went on to have reverse total shoulder arthroplasty. There were no differences in nonunion or reoperation rates among patients with an intact cuff, an impaired cuff, or the presence of shoulder arthroplasty. Discussion and conclusion: Patients with rotator cuff dysfunction or presence of reverse total shoulder arthroplasty are more likely to have acromion stress fractures compared to those with an intact rotator cuff. Surgical fixation of acromion fractures can improve the shoulder range of motion and pain scores. The nonunion rate is lower for surgical fixation compared to existing literature on nonoperative treatment of acromion fractures.